Google Play review analysis of digital mobile applications of Islamic microfinance institutions - Azhar Alam; Ririn Tri Ratnasari; Danang Dwi Nurrochman; Estina Rahmawati (International Journal of Advances in Applied Sciences, 2024)
The study aims to analyze user reviews of Islamic microfinance mobile applications to evaluate their effectiveness for micro, small, and medium-sized enterprises (MSMEs). Using the netnography method, this study collected and analyzed 4,131 reviews from the Google Play Store, focusing on applications with ratings above 4.5. The data was categorized into positive and negative reviews. Key findings indicate that users appreciate 50.42% of positive reviews expressed satisfaction and motivation to advance, 28.90% praised the ease of transactions via the application, and 20.68% appreciated the practical benefits in any payment, while with frequent errors (25.53%), issues with activation codes (21.28%), and transaction failures (17.02%) being the most common complaints. The study recommends improving technical reliability to enhance user satisfaction. Future research should explore user experiences in more diverse digital environments. This research contributes to understanding user perceptions and strengthening the development of Islamic microfinance applications.